Soteriološka aitiologija Logosovega učlovečenja - Bogataj, Jan Dominik (Edinost in dialog, 2023)
In this paper, the author examines the earliest Christian treatise, Athanasius’ De incarnatione, in the light of the subsequent development of theological thought on the incarnation, and more specifically on the causes of the incarnation. The medieval scholastic reflections on the Logos’ incarnation as a good in itself, or as the means of the consummation of our salvation, applied to Athanasius’ work, do not represent a methodological shortcoming of anachronism, but rather help better understand the text itself. Indeed, a close analysis of the text shows that through two key passages in Athanasius’ work (On the Incarnation 1.3; 4.2-3) we can trace the two schematic aspects that would later be highlighted and developed by scholastic theology.
Keywords: cur deus homo; incarnation; patristic theology; patristična teologija; scholasticism; sholastika; učlovečenje; utelešenje